1992
DOI: 10.1111/j.1365-2141.1992.tb03001.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous injection of factor IX for the treatment of haemophilia B

Abstract: Haemophilia B patients are normally treated, either prophylactically or in response to bleeding episodes, by frequent intravenous injections of factor IX purified from blood donors. Here we show in model animal experiments that purified human factor IX, when injected subcutaneously, is rapidly (in 3-11 h) and reasonably efficiently (30-40% of an equivalent intravenous dose) transported at least partly by the lymphatic drainage of the skin into the bloodstream, mostly in a biologically active form. This suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Cheung et al 26 built on the studies of Heimark et al 27 and Stern et al 28 to document that FIX binds to type IV collagen via lysine at position 5 or valine at position 10, identifying the mechanism of extravascular and endothelial binding of hFIX. 26,29,30 The published data [23][24][25] and this report support the hypothesis that FIX can traverse not only from the extravascular space to the systemic circulation but also from the systemic circulation to the extravascular space. Whether or not FIX in the extravascular space has a function For personal use only.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Cheung et al 26 built on the studies of Heimark et al 27 and Stern et al 28 to document that FIX binds to type IV collagen via lysine at position 5 or valine at position 10, identifying the mechanism of extravascular and endothelial binding of hFIX. 26,29,30 The published data [23][24][25] and this report support the hypothesis that FIX can traverse not only from the extravascular space to the systemic circulation but also from the systemic circulation to the extravascular space. Whether or not FIX in the extravascular space has a function For personal use only.…”
Section: Discussionsupporting
confidence: 73%
“…A series of studies that administer the FIX protein subcutaneously have been reported in animals and humans with dosing that ranges from 15 to 200 IU/kg. [23][24][25] All these studies detected measurable FIX in the recipient's plasma following subcutaneous administration. In the study by Liles et al, 25 a single adult patient with hemophilia B (cross-reacting material negative, CRMϪ) given a high-purity plasma-derived hFIX subcutaneously developed a transient, low titer inhibitor (1-2 Bethesda units) months after the clinical study while being treated for a traumatic bleed.…”
Section: Discussionmentioning
confidence: 99%
“…Control experiments show that this is likely to be due to lymphatic drainage of the skin. 7 Alternatively, the low level of expression in vivo may be due to a change in the activity of the promoter controlling expression of the transgene after transplantation. This latter phenomenon of promoter down-regulation has also been proposed as the likely reason for short duration of Correspondence: GG Brownlee, Received 17 July 1997; accepted 27 October 1997 expression in keratinocytes in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that low molecular weight proteins in the extracellular space enter the bloodstream via capillaries, and there is evidence that proteins .16 kDa secreted by the keratinocytes in the epidermis are likely to reach the circulation via lymphatic return (Gerrard et al, 1992).…”
mentioning
confidence: 99%